Economic Implications of Judicial Entanglements: An Empirical Analysis of Land Cases in the Philippines Supreme Court - Candelaria, Sedfrey M (Archīum Ateneo, 2018)
This paper develops a unique dataset of Supreme Court land dispute cases in the Philippines spanning 2002 to 2016. The sample includes 1,409 cases with complete information on the estimated land value (through zonal value estimation), land size, land location, litigation time, and win rate across the case lifecycle. This study is one of the first to leverage such a comprehensive Philippine dataset on these types of cases. Specifically, the objectives of this study are: 1) To estimate the total approximate size and value of the land assets that have been processed in the court system and the length of time they have been tied up in the court system; 2) To analyze the possible factors influencing the speed of resolution of these types of cases, as well as the patterns behind favorable decisions; and, 3) To identify the possible judicial reforms that could try to reduce the time these assets are tied up in courts, thus contributing to the release of land assets for productive investments and utilization in the Philippine economy. The data shows that the average size of the land asset tried in court is about 1.477 million square meters and valued at about P1,790,000,000. The land assets can be tied up in the court system from anywhere between 1-66 years, averaging about 12.574 years in litigation. About 99% of the 1,409 land assets in dispute are private land. In addition, this paper presents evidence that litigation of land disputes in Regions VI, Region XI, Region XII, and the ARMM is associated with a longer litigation time. In addition, higher estimated land asset value is also associated with longer litigation periods.